Decentralized control and filtering in interconnected dynamical systems - Mahmoud, Magdi S. (Boca Raton, Fl. : CRC Press, 2011)
'Based on the many approaches available for dealing with large-scale systems (LSS), this book provides a rigorous framework for studying the analysis, stability, and control problems of LSS while addressing the dominating sources of difficulties due to dimensionality, information structure constraints, uncertainties, and time delays. The author reviews past methods and results from a contemporary perspective, examines current trends and approaches, and offers future improvements to approaches. Providing an overall assessment of current LSS theories, he presents key concepts supported by proofs as well as efficient computational methods'--
Includes bibliographical references and index.
Keywords: Decomposition method; Large scale systems -- Mathematical models; Mechanics, Analytic -- Mathematical models; Intelligent control systems